Формування системи управління інвестиційною діяльністю аграрного підприємства - Вініченко, Ігор Іванович; Vinichenko, I. (Дніпровський державний аграрно-економічний університет, ТОВ `ДКС Центр`, 2019)
Інвестування є однією з узагальнюючих характеристик соціально-економічної ситуації в Україні. Для економіки країни важливе значення має розвиток виробництва і на цій основі збільшення обсягу інвестицій у привабливі галузі. Інвестиції – це передумова суспільного розвитку. В запропонованій статті визначено особливості формування системи управління інвестиційною діяльністю підприємства. Встановлено, що управління формуванням інвестиційних ресурсів включає визначення обсягу інвестованого капіталу, формування власних і позикових інвестиційних ресурсів. Реалізація головної мети і задач здійснення інвестиційної діяльності передбачає виконання певних функцій, які можна розділити на дві групи: загальні функції та специфічні функції. Вважаємо, що найбільш ефективною організаційною структурою управління інвестиційною діяльністю підприємства в сучасних умовах є така, в основі якої знаходяться центр відповідальності, в тому числі й центр інвестицій. Доведено, що управління інвестиційною діяльністю передбачає необхідність проведення фінансових та економічних розрахунків, які пов’язані з потоками грошових коштів в різні періоди часу. Іnvesting is one of the most general characteristics of the socio-economic situation in Ukraine. The development of production is important for the country's economy, and on this basis, an increase in investments in attractive industries. Investments are a prerequisite for social development. The article describes the peculiarities of the formation of a management system for investment activity of an agrarian enterprise. It was established that the management of formation of investment resources includes determination of the volume of invested capital, formation of own and borrowed investment resources. Realization of the main goal and objectives of investment activity involves the implementation of certain functions, which can be divided into two groups: general functions and specific functions. To the general functions we propose to include: development of investment strategy of the enterprise, organizational structures of providing investment activities, information systems supporting the provision of substantiation of alternative options for investment decisions; analysis, planning, control over the implementation of management decisions in the field of investment activity. Specific functions are investment management and the formation of investment resources. The effectiveness of the investment activity of the agrarian enterprise depends to a certain extent on the organizational support, which includes an interconnected set of structural units of the enterprise, which, on the one hand, provide development and decision-making on the management of investment activities, on the other hand, they are fully responsible for the implementation of these decisions. Organizational support is provided on the basis of the management structure of investment activities and depends on the organizational structure adopted by the enterprise. The most effective among such structures is the design and matrix.
Formation of the investment management system activity of agricultural enterprise
Вініченко І. І. ORCID: 0000-0002-9527-1625
Keywords: аграрні підприємства; аgrarian enterprises; ефективність; efficiency; інвестиції; investments; інвестиційний процес; investment process; інвестиційна діяльність; investment activity; система; system; управління; management